Characterization of 13 Accessions of Purslane (Portulaca sp.) from Bogor, West Java, Indonesia - Setiawan, Farensa Ikman Dedi; Aisyah, Syarifah Iis; Krisantini, Krisantini (Journal of Tropical Crop Science, 2016)
Characterization is part of crop the breeding process aims to protect biodiversity and preserve local germplasm. Indonesia has two known species of Portulaca, Portulaca oleracea and P. grandiflora. Thirteen Portulaca accessions have been collected from Bogor area, comprising five accessions of Portulaca oleracea and eight accessions of Portulaca grandiflora. This study was aimed at the characterization of the 13 accessions and was undertaken at Indoflower BLST, Bogor, between October 2015 to February 2016. The results showed a significant difference in the color of flowers between the two species of Portulaca. The most significant difference is the overall appearance of P. oleracea species. Character color and shape of the flowers between the P. grandiflora white (GW) and P. oleracea are similar.  Significant differences between the species exist in relation to the root systems, but the root systems of accessions within each species are generally similar.  The branching characteristics between the two species and among accessions are generally similar, with branches emerging through the base of leaves or nodes.   However, there are differences in the leaf characteristics between the two species. This study has provided information on flower characteristics of P. grandiflora and P. oleraceae which will be valuable for future breeding efforts in Portulaca.